2008
DOI: 10.1021/es801043y
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among K+−Ca2+ Exchange, Sorption of m-Dinitrobenzene, and Smectite Quasicrystal Dynamics

Abstract: The fate of organic contaminants in soils and sediments is influenced by sorption of the compounds to surfaces of soil materials. We investigated the interaction among sorption of an organic compound, cation exchange reactions, and both the size and swelling of smectite quasicrystals. Two reference smectites that vary in location and amount of layer charge, SPV (a Wyoming bentonite) and SAz-1 were initially Ca- and K-saturated and then equilibrated with mixed 0.01 M KCl and 0.005 M CaCl2 salt solutions both wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…This facilitated the specific interactions of polar functional groups (−NO 2 ) of 1,4-DNB with K + and/or polarized cation-bridging water molecules as well as the cation−π interaction between K + and the planar surface of PX, which has an aromatic π–donor system. It also resulted in less obscuration of zeolite surfaces between exchangeable cations and, hence, makes uncharged regions of the basal siloxane surfaces (hydrophobic nanosites) accessible for organics. ,, While for zeolite with too high of a charge density (SiO 2 /Al 2 O 3 ratio of 5.4), the distance between the sorbed cations was very close, with water molecules in the micropores strongly bonded as a result of the overlap of cationic electric effects. Organic sorption was strongly inhibited by both K + and Ca 2+ , because the large hydration shell of metal cations may intrude or shield the sorption sites for organics in pore spaces, with only a very weak sorption at the uncharged regions being allowed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This facilitated the specific interactions of polar functional groups (−NO 2 ) of 1,4-DNB with K + and/or polarized cation-bridging water molecules as well as the cation−π interaction between K + and the planar surface of PX, which has an aromatic π–donor system. It also resulted in less obscuration of zeolite surfaces between exchangeable cations and, hence, makes uncharged regions of the basal siloxane surfaces (hydrophobic nanosites) accessible for organics. ,, While for zeolite with too high of a charge density (SiO 2 /Al 2 O 3 ratio of 5.4), the distance between the sorbed cations was very close, with water molecules in the micropores strongly bonded as a result of the overlap of cationic electric effects. Organic sorption was strongly inhibited by both K + and Ca 2+ , because the large hydration shell of metal cations may intrude or shield the sorption sites for organics in pore spaces, with only a very weak sorption at the uncharged regions being allowed.…”
Section: Resultsmentioning
confidence: 99%
“…This is because they could control clay interlayer environments and interact with sorbed organic contaminants. 18,20,29−31 Previous studies have focused on the hydration effects of metal ions on the sorption behaviors of organics, such as nitroaromatic compounds (NACs), 22,26,30,32,33 pesticides, 20,23 and organic cations (C X H Y N amines), 34,35 in clay−water systems. It has revealed that sorption of organics to minerals that were exchanged with weakly hydrated cations (e.g., K + , Cs + , and NH 4 + ) was significant.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations